The bipolar outflow and disk of the brown dwarf ISO 217 - Joergens, Viki (Astronomy and astrophysics, 2012)
We show that the very young brown dwarf candidate ISO 217 (M6.25) is driving an intrinsically asymmetric bipolar outflow with a stronger and slightly faster red-shifted component based on spectro-astrometry of forbidden [S II] emission lines at 6716 Å and 6731 Å observed in UVES/VLT spectra taken in 2009. ISO 217 is only one of a handful of brown dwarfs and very low-mass stars (M5-M8) for which an outflow has been detected and that show that the T Tauri phase continues at the substellar limit. We measure a spatial extension of the outflow in [S II] of up to ± 190 mas (about ± 30 AU) and velocities of up to ± 40-50 km s-1. We find that the basic outflow properties (spatial extension, velocities, and outflow position angle) are of similar order as those determined in the discovery spectra from May 2007 of Whelan and coworkers. We show that the velocity asymmetry between both lobes is variable on timescales of a few years and that the strong asymmetry of a factor of two found in 2007 might be smaller than originally anticipated when using a more realistic stellar rest-velocity. We also detect forbidden line emission of [Fe II]λ7155 Å, for which we propose as a potential origin the hot inner regions of the outflow. To comprehensively understand the ISO 217 system, we determine the properties of its accretion disk based on radiative transfer modeling of the SED from 0.66 to 24 μm. This disk model agrees very well with Herschel/PACS data at 70 μm. We find that the disk is flared and intermediately inclined (i ~ 45°). The total disk mass of the best-fit model is 4 × 10-6 M⊙, which is low compared to the accretion and outflow rate of ISO 217 from the literature (~). We propose that this discrepancy can be explained by either a higher disk mass than inferred from the model because of strong undetected grain growth and/or by an on average lower accretion rate and outflow rate than the determined values. We show that a disk inclination significantly exceeding 45°, as suggested from Hα modeling and from both lobes of the outflow being visible, is inconsistent with the SED data. Thus, despite its intermediate inclination angle, the disk of this brown dwarf does not appear to obscure the red outflow component in [S II], which is very rarely seen for T Tauri objects (only one other case).